2020
DOI: 10.1039/d0nr05852a
|View full text |Cite
|
Sign up to set email alerts
|

Heterotwin Zn3P2superlattice nanowires: the role of indium insertion in the superlattice formation mechanism and their optical properties

Abstract: Zinc phosphide forms heterotwin superlattices through the inclusion of indium rich layers at the twins. Here we investigate their structure, influence on the optoelectronic properties, and how its non-polar nature impacts the formation mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…With this in mind, we inspected the surface of zigzag nanowires grown by a vapour–liquid–solid (VLS) growth mechanism (as opposed to the vapour–solid (VS) one of SAE) that are terminated with (101) facets, but still exhibit sub-bandgap emission in a similar range as to those calculated here. 14,15,17,72 The VLS grown nanowires did contain small, rotated domains on the surface in crevices with an increased portion of radial VS growth (Fig. S9†).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…With this in mind, we inspected the surface of zigzag nanowires grown by a vapour–liquid–solid (VLS) growth mechanism (as opposed to the vapour–solid (VS) one of SAE) that are terminated with (101) facets, but still exhibit sub-bandgap emission in a similar range as to those calculated here. 14,15,17,72 The VLS grown nanowires did contain small, rotated domains on the surface in crevices with an increased portion of radial VS growth (Fig. S9†).…”
Section: Resultsmentioning
confidence: 98%
“…Previous experimental studies of Zn 3 P 2 , including SAE grown Zn 3 P 2 , 16 have shown transitions or defect levels in the range of 0.14–0.20 eV, 0.25–0.29 eV, and 0.36 eV below the bandgap, which puts them in the potential range of these rotated interfaces. 6,16–18,36,37,39–44,72 While there may be other origins of transitions in this range acting in parallel, these rotated domains are a potential source. With this in mind, we inspected the surface of zigzag nanowires grown by a vapour–liquid–solid (VLS) growth mechanism (as opposed to the vapour–solid (VS) one of SAE) that are terminated with (101) facets, but still exhibit sub-bandgap emission in a similar range as to those calculated here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oscillatory nature of the superlattice is a consequence of the catalysts’ stability on the top facet, which has a cross-section that goes from hexagonal to truncated triangular. 54 When the cross-section becomes more triangular in nature, the normalized surface energy increases. Lowering of the system energy is achieved by the formation of a (hetero)twin that causes the cross-section to return toward a more stable hexagon.…”
Section: Growth and Crystalline Propertiesmentioning
confidence: 99%
“…Lowering of the system energy is achieved by the formation of a (hetero)twin that causes the cross-section to return toward a more stable hexagon. 54 However, zinc phosphide has a tetragonal structure that does not readily form standard twins. Upon closer inspection by AC bright-field (BF) and HAADF-STEM in combination with atomic resolution core-loss electron energy loss spectroscopy (EELS) mapping, we observed that the mirror plane is an indium-rich discontinuity, forming a heterotwin as shown in Figure 3 .…”
Section: Growth and Crystalline Propertiesmentioning
confidence: 99%